Recommendation of Nasogastric Tube Removal in Acute Stroke Patients Based on Videofluoroscopic Swallow Study - Hwang, Jong-Moon (Ann Rehabil Med, 2017)
OBJECTIVE: To evaluate the safety of nasogastric tube (NGT) removal and change to oral feeding with a food thickener for acute stroke patients in whom a videofluoroscopic swallow study (VFSS) confirmed thin liquid aspiration. METHODS: We retrospectively examined data of 199 patients with first stroke who were diagnosed with dysphagia from 2011 to 2015. Swallowing function was evaluated using VFSS. Patients included in this study were monitored for 4 weeks to identify the occurrence of aspiration pneumonia. The penetration-aspiration scale (PAS) was used to assess VFSS findings. The patients were divided into thin-liquid aspiration group (group 1, n=104) and no thin-liquid aspiration group (group 2, n=95). RESULTS: The feeding method was changed from NGT feeding to oral feeding with food thickener (group 1) and without food thickener (group 2). The PAS scores of thin and thick liquids were 6.46±0.65 and 1.92±0.73, respectively, in group 1 and 2.65±0.74 and 1.53±0.58, respectively, in group 2. Aspiration pneumonia developed in 1.9% of group 1 and 3.2% of group 2 (p=0.578), with no significant difference between the groups. CONCLUSION: We concluded that removing the NGT and changing to oral feeding with a food thickener is a safe food modification for acute stroke patients with thin liquid aspiration. Therefore, we recommend that VFSS should be conducted promptly in acute stroke patients to avoid unnecessary prolonged NGT feeding.